Simultaneous evaluation of volumes and synergistic motion of the left ventricle from X-ray angiograms using a unified computational framework (2019)
X-rays angiograms of the left ventricle as the main cavity of the human heart are acquired at the catheterization rooms routinely in order to evaluate the cardiac dynamic function. The global measurement of volumes, ejection fraction and synergistic motion associated with the ventricular cavity are considered in the assessment of such function. A precise left ventricle silhouette on the angiograms is necessary to calculate the function descriptors. A segmentation method is required to obtain the projected cavity shape